INNV-16. SPINAL POST-TREATMENT SURVEILLANCE IN MEDULLOBLASTOMA – A SYSTEMATIC REVIEW OF THE LITERATURE AND CLINICAL TRIALS. (14th November 2022) - Park, Christopher; Packer, Roger; Rood, Brian; Kilburn, Lindsay; Bornhorst, Miriam; Rossi, Christopher; Fonseca, Adriana; Hwang, Eugene
Abstract: BACKGROUND: Monitoring for dissemination in medulloblastoma involves spinal MRIs (sMRIs) and lumbar punctures (LPs). The frequency and duration of these studies vary depending on risk of dissemination; general practice varies between and within institutions. Our goal is to review the current practice in post-treatment monitoring via examination of published data, clinical trial standards, and expert practice. METHODS: We reviewed the available literature and accessible clinical trial protocols. Using PRISMA guidelines, we conducted searches of Ovid MEDLINE, Embase, and PubMed to identify studies which detailed relapse rates and patterns, and recommended practice for patients with medulloblastoma aged 3-21 years. Eligible studies from 1990 to present were included. RESULTS: Thirteen multi-institutional clinical trials from North America and Europe were analyzed for frequency of post-therapy surveillance with LPs/sMRIs. Several studies (n=8) recommend LPs/sMRIs every 3-6 months in standard risk and every 3 months in high risk disease for two years when initially completing therapy, and then often diverge in frequency after 2 years. Some studies (n=5) did not include post-treatment recommendations. Cumulative data on relapse from available clinical trial reports and single institution studies (n=673 relapses) demonstrated local failure rate of 18.4%, distant failure of 49.1%, and combined distant and local failure of 32.5%. Spine-only relapses were reported to occur in approximately 13-20%, with one small study reporting spine-only relapse rate of 37.5%. DISCUSSION: Patterns of recurrence in medulloblastoma have shifted over time as therapeutic approaches have evolved, including more spinal-only recurrences. Standardized guidance regarding surveillance could have significant impact on clinical detection and streamline management to minimize unnecessary examinations. Early detection of recurrent disease could optimize treatment options for providers and families, whether focusing on curative approaches or quality of life.